Enhancing Self-compassion in Athletes: A Feasibility Study of an Online Self-compassion Program for Athlete Mindfulness, Anxiety and Performance - Flegar, Alaina (Université d'Ottawa / University of Ottawa, 2021)
The nature of sport competition involves athletes being compared and ranked based on athletic ability, with athletes invariably confronted by potential threat of subjective and objective failure within their sport context. Given this circumstance and the extraordinary amount of pressure athletes often experience, developing an ability to be kind towards oneself in the face of perceived failure could be an important part of sport training. This study evaluated the feasibility and preliminary efficacy of a 4-week self-guided online self-compassion program for athletes. Eighty competitive athletes who participate in time-based sports were recruited from sport organizations and randomly assigned to either a 4-week self-compassion program or a wait-list control. Participants in both groups completed pre- and post-study self-report measures of self-compassion, mindfulness, general anxiety, sport-related anxiety, and perceived sport performance. Objective athletic performance was obtained through performance logs. Results indicated that the self-compassion program was of interest to sport organizations and athletes. However, attrition was high and there were challenges with program adherence. Linear mixed model analyses revealed that relative to the wait-list control, participants in the self-compassion group demonstrated significantly greater improvement in overall levels of self-compassion, the self-compassion element of common humanity, and the mindfulness facet Observe. No significant differences between the groups were found for measures of anxiety and perceived and objective sport performance. Factors influencing compliance with online self-compassion programs such as participant readiness and fears of self-compassion are explored. Program efficacy, study limitations, and directions for future research are also discussed. While the self-compassion program is feasible, challenges in program adherence need to be addressed in future studies. Future research should continue formulating the concept of self-compassion in sport to reflect the needs and interests of athletes, consider including several formats and methods of program delivery, add a motivational component to address barriers to participation and program adherence, and work in collaboration with sport coaches and teams.
Keywords: Self-compassion; Sport